(untitled) (International journal of artificial intelligence, 2026)
Pedagogical activities encompass the structured organization of teaching-learning processes and systematic evaluation to ensure effective knowledge acquisition, skill development, and personal growth. This article explores various types of organization in pedagogical activities, including traditional class-lesson systems, innovative and non-traditional forms, and their integration in modern educational contexts. It also examines evaluation methods—formative, summative, diagnostic, and others—along with their roles in enhancing educational outcomes. Drawing on both international best practices and Uzbek pedagogical literature, the study highlights how effective organization and evaluation contribute to student-centered learning, teacher professional development, and alignment with national education reforms in Uzbekistan. The analysis reveals the importance of integrating traditional and modern approaches for quality assurance in education. Key findings emphasize the need for continuous improvement, technology integration, and culturally relevant assessment strategies.